2019
DOI: 10.1177/2055207619867223
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment via social media: advantages and potential biases

Abstract: Background: Adolescent and young adult (AYA) cancer survivors are under-represented in research. Social media is increasingly used for recruitment given its ability to reach large audiences. Differences in participant characteristics and potential biases due to recruitment source are not well understood. Purpose: This study aimed to: (a) compare recruitment strategies (hospital-based v. social media) in enrollment metrics, and (b) among enrolled participants, evaluate group differences in patient characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
96
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 39 publications
1
96
3
Order By: Relevance
“…3,34,35 The Facebook system can reveal users' private information that has not been disclosed to other users by displaying comments and tags on the advertisements or by leaving an unconscious online trail. 35,36 To promote an ethical recruitment process and prevent any unintentional harm to potential participants, researchers should be fully informed of the latest Facebook policies, design the best suited recruitment modality, and discuss wordings in the advertisements with the pertinent IRBs at the early stages of their research. 35 In addition, researchers should clearly understand how social media data is presented, carefully review social media research policies and guidelines such as Internet Research Ethics 3.0 37 and hold frequent discussions with the IRB to provide maximum privacy protection for their participants.…”
Section: Discussionmentioning
confidence: 99%
“…3,34,35 The Facebook system can reveal users' private information that has not been disclosed to other users by displaying comments and tags on the advertisements or by leaving an unconscious online trail. 35,36 To promote an ethical recruitment process and prevent any unintentional harm to potential participants, researchers should be fully informed of the latest Facebook policies, design the best suited recruitment modality, and discuss wordings in the advertisements with the pertinent IRBs at the early stages of their research. 35 In addition, researchers should clearly understand how social media data is presented, carefully review social media research policies and guidelines such as Internet Research Ethics 3.0 37 and hold frequent discussions with the IRB to provide maximum privacy protection for their participants.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] In addition, recent studies have highlighted the impact of social media on the potential recruitment of applicants. [18][19][20] Therefore, we sought to evaluate the accessibility and quality of available information to potential applicants by analyzing the most commonly used web resources and social media outlets for applicants applying to microsurgery fellowship. Overall, we found that both the accessibility and quality of information available to the applicant are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Social media easily connects people for personal communications as well as business-related reasons. Proper use of the platform could increase productivity and e ciency in a society (17). Meanwhile, social media disadvantages exist in the shape of behavioural addiction tendencies existing in some of the users (18).…”
Section: Discussionmentioning
confidence: 99%